Castleman's disease and primary effusion lymphoma in a HIV-positive patient. (May 2014) - Scott, Michael J; Chihada Alhariri, Bashar; Farghaly, Hanan; Perez, Rafael; Arnold, Forest W
We present a case of primary effusion lymphoma (PEL) occurring simultaneously with Castleman's disease in the same patient. Castleman's disease is distinct from PEL, although both are associated with HHV-8. Other cases have debated whether the coexistence of PEL and Castleman's disease is a recurrence of an original PEL tumour in an extracavitary site, or a secondary HHV-8-associated lymphoma distinct from primary PEL. Our case, along with those described previously, show that co-occurrence of PEL and Castleman's disease is possible and plausible. PEL needs to be included in the differential diagnosis in any HIV-positive patient who presents with a pleural effusion, and diagnosis requires only a simple thoracentesis and appropriate immunohistochemistry.